Prototype of Smart Chicken Poultry with IoT Monitoring - Hidzir, Muhammad Khairul Farihin; Ismail, Muhammad Nafis (Evolution in Electrical and Electronic Engineering, 2022)
As the Malaysian population keeps increasing, the demand for poultry meat and egg products will keep rising too. To fulfill this poultry demand in Malaysia, one of the options for increasing chicken poultry output product is to build a systematic farm for the poultry chicken. The implementation of Internet of Things (IoT) in poultry chicken will allow a real-time monitoring of the cage by the internet. Blynk software will be used to link the poultry cage with the electronic processor via ESP8266. The growth efficiency of poultry chicken will be monitored and can be measured by using the Feed Consumption Ratio (FCR) method. Some of the sensors are attached to help the ESP8266 to collect the data on the poultry chicken. Temperature and humidity sensor (DHT11), ultrasonic and water level sensor to detect food and water level. Also, this poultry system is built with an alarm notifying system. The abnormal condition for the poultry chicken such as high or low temperature, low food and water level, and the operation of the food motor will notify the user about the problem that occurs on the farm. The collected data is sent to a cloud-based server, Blynk software where it is kept in a database and the result can be used for analysis.